Mercantilização da cultura e dinâmica simbólica local: a indústria cultural em Itabira, Minas Gerais - Luiz Alex Silva Saraiva (2009)
Gradual transference of cultural public policies to private agents contributes to transformation of culture into commodity. We defend the thesis that particularization of public policies converts culture into cultural industry, something with exchange value more than use value, used to social hegemony maintenance. So, our intent is to analyze relations between culture commoditization and local symbolic dynamics, what was made through a qualitative study, based on nominalist ontology, a humanist epistemology, and inductive method. Out researchwas a case study in a city-organization, Itabira (Brazil), in what we used primary and secondary data sources associated to direct observation. Primary data was collected through twelve deep individual interviews with representants from segments of local society; all of them full recorded and transcript. Secondary one included culture official documents, CarlosDrummond de Andrade poems on Itabira, and pictures of local cultural artifacts. While whole written data were analyzed through French discourse analysis, pictures were through semiotics analysis, when they were not just illustrations. Main results suggest that at this ityorganizationthere are strong identity references of people and city. We also observe agrowing process of culture commoditization, with clear and clear economic exploration actions using Drummond. He lends his name to many local cultural products, whose content is influenced by a privatization of culture. This is spread in an excluding way, and carrying anelitist cultural ideology, that people should assume as yours. Local symbolic dynamics has three main moments. Past symbolism, lyrically described in the poets work, it refers to yesterday overcome; present one, in what economical strength comes from the Vale and from mining exploration; and Future symbolism, which indicates Drummond as main reference. We concluded that, although there is the intention of culture becomes the most important economic activity into the future, this process is still beginning. In part this is because public sector amateurism, and also because the poet no to be considered representative of popular culture, but just what elite desire. Its economic appropriation, so, does not have correspondence in symbolic level, resulting in an unwritten page of Itabiras future.